Ultrastructural Evidence That Intracellular Ice Formation and Possibly Cavitation Are the Sources of Freezing Injury in Supercooling Wood Tissue of Cornus florida L. - Ristic, Z. (1993)
Although cellular injury in some woody plants has been correlated with freezing of supercooled water, there is no direct evidence that intracellular ice formation is responsible for the injury. In this study we tested the hypothesis that injury to xylem ray parenchyma cells in supercooling tissues is caused by intracellular ice formation. The ultrastructure of freezing-stress response in xylem ray parenchyma cells of flowering dogwood (Cornus florida L.) was determined in tissue prepared by freeze substitution. Wood tissue was collected in the winter, spring, and summer of 1992. Specimens were cooled from 0 to -60[deg]C at a rate of 5[deg]C h-1. Freezing stress did not affect the structural organization of wood tissue, but xylem ray parenchyma cells suffered severe injury in the form of intracellular ice crystals. The temperatures at which the ice crystals were first observed depended on the season in which the tissue was collected. Intracellular ice formation was observed at -20, -10, and -5[deg]C in winter, spring, and summer, respectively. Another type of freezing injury was manifested by fragmented protoplasm with indistinguishable plasma membranes and damaged cell ultrastructure but no evidence of intracellular ice. Intracellular cavitation may be a source of freezing injury in xylem ray parenchyma cells of flowering dogwood.